An Advantages of Internet Marketing in Digital Tourism - Khurramov Ortikjon Kayumovich (Research Parks Publishers, 2021)
The article discusses an advantages of internet marketing in digital tourism. Among the main advantages of using the Internet when conducting marketing research is the speed of research; the ability of respondents to participate in the study at a time convenient for them, interrupting the survey, if necessary; accessibility of respondents regardless of the region of their residence; the respondent’s identity is not influenced by the personality of the interviewer; use of visual materials